PERLINDUNGAN KONSUMEN TERHADAP HAK KONSUMEN ATAS KEAMANAN DALAM MENGKONSUMSI BARANG DARI TINDAKAN PENGOPLOSAN BERAS - Inne Christina; Ermanto Fahamsyah (Fakultas Hukum Universitas Tarumanagara, 2018)
The proceedings of low-quality mixing of rice poses a threat to consumers. Article 4 UUPK states the consumer rights of safety and protection in consuming a product, receiving correct information, honest and true, and enables compensation of the item received is incorrect. Article 7 states the obligation of the company to show good faith in carrying out their responsibility and guarantee the quality of their product, ensuring they meet the standards accordingly. Violations also happen according to Food Regulation. In order to avoid futher violations, the government should supervise the operations of the market trade. Additionally, what kind of legal protection towards the consumers rights regarding the safety of consuming products from the low-quality mixing of rice and what is the role of the government in supervising such kind of distribution? This research will list out the problems addressed by using normative methods. Research data will observe the existing legal prodictions of UUPK and Food Regulation by suggesting sanctions to companies that violate the policies of UUPK and Food Regulation, as well as the supervision of the government as stated in PERMENDAG No. 20 Tahun 2009.